Evaluation of cannabidiol-based products in Brazil: how can current regulations influence their labeling quality? - Andrea Donatti Gallassi; André Wagner Carvalho de Oliveira; Nathália Silva Mendes; Renato Filev; Eduardo Yoshio Nakano (Journal of Cannabis Research)
Abstract There is concern about the quality of cannabis-based products used in Brazil, mainly cannabidiol (CBD). This study aimed to evaluate the quality of labeling on CBD products marketed in Brazil authorized by two regulations – N660/2022 on imported products and N327/2019 on products with temporary trade permits – and whether there were differences between them concerning four domains: prescription, good manufacturing practices (GMP), laboratory tests, and safety of use. Determined labeling quality was based on a score of 45 criteria divided per domain and weights from 1 to 3 (according to the relevance for users' and prescribers' safety) built by public information provided by product manufacturers/representatives on websites and e-mail consultations. The quality score was classified as very satisfactory, satisfactory, or not very satisfactory, represented in median and interquartile range. Between the N327 and N660 products, the quality scores were compared using the Mann–Whitney U-test. All tests considered two-tailed hypotheses and a significance level of 5%. After applying the inclusion criteria, from 148 products selected, 105 were evaluated. Most of the evaluated CBD products were classified as satisfactory (47), followed by not very satisfactory (39) and very satisfactory (19). The N327 products presented information that was more accessible than the N660 products. Similarly, there was a significant difference between the two groups concerning the domains of prescription and safety of use; products in the N327 showed better results than those in the N660. This study contributes to the urgent debate on the quality of labeling and the risks of CBD widely marketed in Brazil.